Research and Analysis of Heavy Metal Content in Children's Footwear - Jinning ZHU; Bao LIU (Pige Kexue Yu Gongcheng)
With the development of society and the progress of science and technology, parents pay more attention to the healthy growth of children. In this study, a total of 303 batches of children's footwear were collected from production and circulation, and 455 samples were tested for heavy metal contents according to different materials and parts. The samples were roughly divided into synthetic leather, textile, leather and plastic according to materials, and upper, lining and inner pad according to parts. The detection rate, content and unqualified situation of heavy metals in samples were studied, and whether there were significant differences among samples was further analyzed. The results demonstrated that the detection rate of lead was higher than that of cadmium, and the samples made of plastic materials and the upper were usually found to be unqualified (Both of lead and cadmium exceeded the limit requirements). One-way ANOVA showed that there was no significant difference in the contents of heavy metals among different parts of children's shoes, and the difference was mainly reflected in different materials. The research content provides some data support for the safety of heavy metals in children's footwear and related products.